2015
DOI: 10.3906/zoo-1401-13
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence and temporal variation in the size-frequency distribution of2 bloom-forming jellyfishes, Catostylus perezi (L. Agassiz, 1862) and Rhizostoma pulmo (Cuvier, 1800), in the Indus Delta along the coast of Sindh, Pakistan

Abstract: Blooms of jellyfishes were studied at 3 sites, namely Bhanbore, Mirpur

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…Very small, and illegal, mesh sizes (3.75-7.5 mm) are used in the netting of these gears (Waryani et al 2015) which retain every life form that enters in the range of these fishing gears including juvenile and undersized fishes (Ahmad and Hasan 1997). In the post-monsoon season, around 100-200 beach seine and estuarine bag nets are regularly operated in the surrounding areas of Keti Bandar.…”
Section: Study Areamentioning
confidence: 99%
“…Very small, and illegal, mesh sizes (3.75-7.5 mm) are used in the netting of these gears (Waryani et al 2015) which retain every life form that enters in the range of these fishing gears including juvenile and undersized fishes (Ahmad and Hasan 1997). In the post-monsoon season, around 100-200 beach seine and estuarine bag nets are regularly operated in the surrounding areas of Keti Bandar.…”
Section: Study Areamentioning
confidence: 99%
“…Recently, Lee et al (2013) and Prieto et al (2013) confirmed the validity of the morphological classification of R. pulmo as a separate species. As it's known, few demographic (Galil 2000, Kogovšek et al 2010, ecological (Lilley et al 2009, Gili et al 2009) and biological (Fuentes et al 2011, Purcell et al 2012, Waryani et al 2015 Here, phylogenetic analyses of R. pulmo were conducted on more samples collected along the Tunisian Coast, using sequences of mtDNA COI gene to: 1) describe in details the genetic diversity of R. pulmo in this region and 2) compare the present results with that previously published by Ramšak et al (2012) and Armani et al (2013) to check whether or not there is a recent evidence of genetic differentiation occurred by this species in the three biogeographic regions, Tunisian Coast, North Adriatic and Western Mediterranean. Table S1).…”
Section: Introductionmentioning
confidence: 99%